Allogeneic haematopoietic cell transplantation for myelofibrosis: proposed definitions and management strategies for graft failure, poor graft function and relapse: best practice recommendations of the EBMT Chronic Malignancies Working Party - McLornan, Donal P.; Hernandez-Boluda, Juan Carlos; Czerw, Tomasz; Cross, Nicholas; Joachim Deeg, H.; Ditschkowski, Marcus; Moonim, Mufaddal T.; Polverelli, Nicola; Robin, Marie; Aljurf, Mahmoud; Conneally, Eibhlin; Hayden, Patrick; et al. (Leukemia, 2021)
Allogeneic haematopoietic cell transplantation (allo-HCT) remains the only curative approach in myelofibrosis (MF). Despite advances over recent decades, relapse and non-relapse mortality rates remain significant. Relapse rates vary between 15 and 25% across retrospective studies and management strategies vary widely, ranging from palliation to adoptive immunotherapy and, in some cases, a second allo-HCT. Moreover, in allo-HCT, there is a higher incidence of poor graft function and graft failure due to splenomegaly and a hostile “pro-inflammatory” marrow niche. The Practice Harmonisation and Guidelines subcommittee of the Chronic Malignancies Working Party (CMWP) of EBMT convened an international panel consisting of transplant haematologists, histopathologists and molecular biologists to propose practical, clinically relevant definitions of graft failure, poor graft function and relapse as well as management strategies following allo-HCT. A systematic approach to molecular monitoring, histopathological assessment and chimerism testing is proposed. These proposed recommendations aim to increase the accuracy and uniformity of reporting and to thereby facilitate the development of more consistent approaches to these challenging issues. In addition, we propose management strategies for these complications.